An in vitro assessment of biaxial flexural strength, degree of monomer conversion, color stability, and ion release in provisional restorations containing Sr-bioactive glass nanoparticles - Chawal Padunglappisit; Napassorn Suwanprateep; Harit Chaiwerawattana; Parichart Naruphontjirakul; Piyaphong Panpisut (Medical Journals Sweden, 2023)
AbstractThis study examined the mechanical and chemical properties of an experimental provisional restoration containing Sr-bioactive glass nanoparticles (Sr-BGNPs) compared to commercial provisional materials. The experimental material (TempS10) contained dimethacrylate monomers with added 10 wt% Sr-BGNPs. The degree of monomer conversion (DC) of self-curing (n = 5), biaxial flexural strength (BFS)/modulus (BFM) (n = 5), and color changes (ΔE*00) of materials in red wine (n = 5) were determined. Additionally, ion release (Ca, P, and Sr) in water at 2 weeks was examined (n = 3). The commercial materials tested included polymethyl methacrylate-based provisional material (Unifast) and bis-acrylic materials (Protemp4 and Cooltemp). TempS10 exhibited a comparable degree of monomer conversion (49%) to that of Protemp4 (60%) and Cooltemp (54%) (p > 0.05). The DC of Unifast (81%) was significantly higher than that of other materials (p < 0.05). TempS10 showed a BFS (126 MPa) similar to Cooltemp (102 MPa) and Unifast (123 MPa), but lower than Protemp4 (194 MPa). The immersion time for 2 weeks exhibited no detrimental effect on the strength and modulus of all materials. The highest ΔE*00 at 24 h and 2 weeks was observed with TempS10, followed by Cooltemp, Unifast, and Protemp4. Only TempS10 showed a detectable amount of Ca (0.69 ppm), P (0.12 ppm), and Sr (3.01 ppm). The experimental provisional resin restoration containing Sr-BGNPs demonstrated polymerization and strength comparable to those of bis-acryl provisional restorations but with the added benefit of ion-releasing properties. However, the experimental material demonstrated unsatisfactory color stability.